DEVELOPING E-SCATTERGORIES GAME IN WRITING DESCRIPTIVE TEXT FOR THE TENTH GRADE IN VOCATIONAL SCHOOL - Julita Ennis; Rahmad Husein (Universitas Negeri Medan, 2021)
The objective of this study is to develop E-Scattergories game as a media to teach writing descriptive text for the tenth grade students in SMK Namira Tech Nusantara Medan. This study was conducted by using Research and Development design through six stages; gathering data and information, need analysis, designing materials and media, validating, revising, get the product. The subject of the study was tenth grade students and the English teacher in SMK Namira Tech Nusantara Medan. The data were gathered by reviewing documents, conducting interview to English teacher and distributing questionnaires to TKJ 1 (Teknik Komputer Jaringan) consisting of 18 students to get the students’ need. The interview and questionnaire results proved that the students to neededdigital game as a media. The developed writing materials were validated by two experts with the average scores of 92.66 of 100. It shows that the E-Scattergories game is valid and suitable to be used for the tenth grade students in SMK Namira Tech Nusantara Medan. The final product can be used from EScattergories developer.egoarchitect.com.Key words: development, E-Scattergories game, digital game, descriptive text.